"The biggest hire in school history" : considering the factors influencing the hiring of a major college football coach - Hambrick, Marion E.; Bass, Jordan R.; Schaeperkoetter, Claire C. (London : Human Kinetics, Inc., 2014)
The purpose of this case is to illuminate the numerous factors administrators must consider when conducting and completing a coaching search. Specifically, participants are instructed to use Kellison's (2013) ethical decision-making process framework to guide their analysis when deciding on, and eventually hiring, a head coach at an exceedingly visible university and athletic department. A hypothetical situation was created based on actual events that took place during a highly publicized head coach search in a major university football program. In all, participants will be immersed in the process of identifying, interviewing, and ultimately choosing a new head coach for their highest revenue-generating program during the most important time in the history of the university and athletic department.
Originally published in Hambrick, M.E., Bass, J.R., & Schaeperkoetter, C.C. (2014). "The Biggest Hire in School History": Considering the factors influencing the hiring of a major college football coach. Case Studies in Sport Management, 3(1), 82-92. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Football coaches -- Selection and appointment; Sports administration